2021
DOI: 10.1038/s42003-021-02254-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma methionine metabolic profile is associated with longevity in mammals

Abstract: Methionine metabolism arises as a key target to elucidate the molecular adaptations underlying animal longevity due to the negative association between longevity and methionine content. The present study follows a comparative approach to analyse plasma methionine metabolic profile using a LC-MS/MS platform from 11 mammalian species with a longevity ranging from 3.5 to 120 years. Our findings demonstrate the existence of a species-specific plasma profile for methionine metabolism associated with longevity chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 95 publications
2
10
0
Order By: Relevance
“…Signi cantly, different ndings seem to indicate that the compositional observation at protein level can be extended to the free methionine form. Thus, available evidences related to free methionine and longevity demonstrate lower concentrations of free plasma methionine in long-lived species [47] and exceptionally longevous animal species like naked-mole rat [17,42]. In this context, our study reported the existence of a species-speci c tissue (heart) pro les and association with longevity for metabolites belonging to the methionine metabolism.…”
Section: Discussionsupporting
confidence: 56%
“…Signi cantly, different ndings seem to indicate that the compositional observation at protein level can be extended to the free methionine form. Thus, available evidences related to free methionine and longevity demonstrate lower concentrations of free plasma methionine in long-lived species [47] and exceptionally longevous animal species like naked-mole rat [17,42]. In this context, our study reported the existence of a species-speci c tissue (heart) pro les and association with longevity for metabolites belonging to the methionine metabolism.…”
Section: Discussionsupporting
confidence: 56%
“…Significantly, different findings seem to indicate that the compositional observation at the protein level can be extended to the free methionine form. Thus, available evidence related to free methionine and longevity demonstrates lower concentrations of free plasma methionine in long-lived species [ 23 ] and exceptionally longevous animal species like the naked mole rat [ 19 , 36 ]. In this context, our study reported the existence of species-specific tissue (heart) profiles and association with longevity for metabolites belonging to methionine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Heart metabolite extraction was performed based on a previously described method [ 23 ]. Briefly, 10 µL of sample homogenates were added to 30 µL of cold methanol containing 1 μg/mL of Phe- 13 C as an internal standard and 1 μM BHT as an antioxidant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic manipulations leading to methionine restriction yield similar results [ 56 , 57 , 58 , 69 ]. Interestingly, a comparative study of plasma methionine metabolic profile among 11 mammalian species whose lifespans range from 3.5 to 120 years revealed a correlation of longevity with reduced methionine and cystathionine levels [ 106 ]. Methionine restriction (MR) is proposed to reproduce some of the metabolic consequences of CR.…”
Section: One-carbon Metabolism In Agingmentioning
confidence: 99%